COMPETENCE, MOTIVATION AND DISCIPLINE ON PERFORMANCE OF COMMUNITY AND VILLAGE EMPOWERMENT OFFICES - Dean Seshar Rahmadina; Weti Kurniawati (Journal Of Resource Management, Economics And Business, 2022)
Purpose: This study aims to determine the effect of competence, motivation and discipline on employee performance Research Methodology: The research method used is quantitative, data collection is done by means of observation and questionnaires. The population in this study were employees of the Office of Community and Village Empowerment, as many as 30 people became the sample. Measurement using a Likert scale. Testing the data using SPSS with Validity, Reliability, Classical Assumption Test, Termination Test, and Hypothesis Testing. Results: The R Square value of 0.993 or equal to 99.3% means that the independent variables Competence (X1), Motivation (X2), and Discipline (X3) affect the dependent variable Performance (Y) by 99.3%. While the remaining 0.7% is influenced by other variables outside this regression equation or variables that are not examined. From the results of calculations using SPSS, the value for calculated F is 1.250 while the F table value is 0.95, which means the calculated F value > F table. The significance value obtained is 0.000, which means sig <0.05. This shows that there is a significant effect of the independent variable simultaneously on the dependent variable, so that H0 is rejected, which means that there is a positive and significant influence between competence (X1), motivation (X2), and discipline (X3) on employee performance (Y). It can be concluded that competence, motivation and work discipline have a positive and significant effect on employee performance. Limitations: Need to be reviewed regarding the factors that affect employee performance other than motivation, discipline and competence. Testing of subjects and research populations is expanded not only in one place. Contribution: This research is expected to be useful for adding insight, knowledge about the influence of competence, work motivation, and discipline on employee performance and can be used as empirical support related to similar research for academics.